An efficient co-culture of Halomonas mongoliensis and Dunaliella salina for phenol degradation under high salt conditions - Wang, Changjian; Guo, Haiqiao; Yu, Peng; Huang, Bo; Xin, Zhikun; Zheng, Xufan; Zhang, Jinli; Tang, Tao (Frontiers in Microbiology, 2024)
Phenol is one of the major organic pollutants in high salt industrial wastewater. The biological treatment method is considered to be a cost-effective and eco-friendly method, in which the co-culture of microalgae and bacteria shows a number of advantages. In the previous study, a co-culture system featuring Dunaliella salina (D. salina) and Halomonas mongoliensis (H. mongoliensis) was established and could degrade 400 mg L−1 phenol at 3% NaCl concentration. In order to enhance the performance of this system, D. salina strain was subjected to adaptive laboratory evolution (ALE) by gradually increasing the phenol concentration from 200 mg L−1 to 500 mg L−1 at 3% NaCl concentration. At a phenol concentration of 500 mg L−1, the phenol removal rate of the resulting D. salina was 78.4% within 7 days, while that of the original strain was only 49.2%. The SOD, POD, and MDA contents of the resulting strain were lower than those of the original strain, indicating that the high concentration of phenol was less harmful to the resulting strain. A co-culture system was established with the resulting D. salina and H. mongoliensis, which could complete degrade 500 mg L−1 of phenol within 8 days, outperforming the original D. salina co-culture system. This study proved that ALE could improve the phenol tolerance and phenol degradation capability of D. salina, and then effectively improve the phenol degradation capability of D. salina and H. mongoliensis co-culture system.